The use of phage FCL-2 as an alternative to chemotherapy against columnaris disease in aquaculture - Laanto, Elina; Bamford, Jaana K. H.; Ravantti, Janne J.; Sundberg, Lotta-Riina (Frontiers in Microbiology, 2015)
Flavobacterium columnare, the causative agent of columnaris disease in fish, causes millions of dollars of losses in the US channel catfish industry alone, not to mention aquaculture industry worldwide. Novel methods are needed for the control and treatment of bacterial diseases in aquaculture to replace traditionally used chemotherapies. A potential solution could be the use of phages, i.e., bacterial viruses, host-specific and self-enriching particles that can be can easily distributed via water flow. We examined the efficacy of phages to combat columnaris disease. A previously isolated phage, FCL-2, infecting F. columnare, was characterized by sequencing. The 47 142 bp genome of the phage had G + C content of 30.2%, and the closest similarities regarding the structural proteins were found in Cellulophaga phage phiSM. Under controlled experimental conditions, two host fish species, rainbow trout (Oncorhynchus mykiss) and zebrafish (Danio rerio), were used to study the success of phage therapy to prevent F. columnare infections. The survival of both fish species was significantly higher in the presence of the phage. Hundred percent of the zebrafish and 50% of the rainbow trout survived in the phage treatment (survival without phage 0 and 8.3%, respectively). Most importantly, the rainbow trout population was rescued from infection by a single addition of the phage into the water in a flow-through fish tank system. Thus, F. columnare could be used as a model system to test the benefits and risks of phage therapy on a larger scale.